Impact of Industry 4.0 Adoption on Eco-Innovation and Sustainable Development: The Automotive and Aerospace Manufacturing Sectors - Maldonado Guzman, Gonzalo (Mercados y Negocios, 2026)
This study aims to fill a gap in the literature and provide robust empirical evidence on the effects of IoT 4.0 on eco-innovation and the sustainable development of manufacturing companies by conducting a survey of 378 manufacturing companies in the automotive and aerospace industries in Mexico and validating the results using PLS-SEM. The results suggest that the adoption of Industry 4.0 has significant positive effects on both sustainable development and eco-innovation, that eco-innovation has a considerable positive impact on sustainable development, and that eco-innovation also serves as a mediating mechanism between Industry 4.0 and sustainable development.